(untitled) - Hawley, Chris (Australia, 2002)
Hazardous Materials Air Monitoring/Detection Devices provides HazMat teams with a thorough guide to effective air monitoring in emergency response situations. The key component to safely responding to hazardous materials is the use of a variety of detection devices for effective air monitoring. In this book, each type of air monitoring device available for emergency services is described in detail, including operating guidelines and sampling strategies. The most up-to-date information is provided along with discussion of the future trends and technology shaping this business, keeping the user at the forefront of this rapidly changing field. Also, a special section discusses the latest trend in HazMat-the detection and monitoring of hazardous agents used for terrorism. (Keywords: Hazmat)
Keywords: Air,Hazardous substances,Chất độc nguy hiểm,Không khí; Pollution,Measurement,Ô nhiễm,Đo lường